Ionization effect and displacement effect induced photoresponsivity degradation on α-In2Se3 based transistors for photodetectors. (September 2020) - Hou, Pengfei; Wang, Chenlu; Chen, Yun; Zhong, Qing; Zhang, Yuke; Guo, Hongxia; Zhong, Xiangli; Wang, Jinbin; Ouyang, Xiaoping
Abstract: Two-dimensional (2D) van der Waals (vdW) materials-based photodetectors have attracted great attention because of quick response time, excellent photoresponsivity and high light/dark current ratio. α-In2 Se3 is one of the interesting 2D vdW materials for photodetectors because of the interrelated in-plane (IP) and out-of-plane (OOP) polarizations. It has been demonstrated that the polarizations can be used to regulate photoresponsivity of the α-In2 Se3 nanoflakes based photodetectors. In addition, domain evolution may be related to the photoresponsivity degradation when the α-In2 Se3 nanoflakes based photodetectors are in radiation environment. However, it is still unclear the effect of ionization and displacement damage on photoresponsivity induced by radiation particles. In this article, the α-In2 Se3 based transistors for photodetectors are exposed in the 60 Co γ-rays environment to induce the photoresponsivity degradation, all the channel width is about 95–100 μm for observing significant radiation effects. In order to investigate the intrinsic photoresponsivity degradation of the α-In2 Se3 based transistors, a 405 nm laser is used as the light source to measure the photoresponsivity. The photoresponsivity of the devices is significantly degraded with increasing irradiation dose. Besides these, the dark current and Se atoms ratio decrease as the increasing of total dose. It may show complicate coupling radiation effect that the domain evolution induced by both the ionization effect and displacement effect promotes the photoresponsivity degradation. After a total dose of 1 Mrad (Si) 60 Co γ-rays, the photodetector can still be used to detect the light with a high photoresponsivity of about 107 A/W when the input optical power density is about 454 μW/cm 2 . Our results may promote the investigation of radiation effect in 2D vdW materials-based photodetectors. Highlights: Photoresponsivity degeneration induced by total dose effect. Displacement effect is displayed as changes in atomic ratio. Ionization effect induced domain evolution in 2 d ferroelectric materials.